Pengendalian Intern Pendapatan Pada Layanan Jasa Pospay Loket PT Pos Indonesia KCU Jember - Umattul Khoiriyah, Julaikha; Reviandani, Wasti (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
Efficient internal control is essential for companies. The main objective of internal control is to build efficient control systems within a company or organisation to improve operational procedures. The aim of this study is to determine the payment system and methods for bill payment utilising Pospay in order to improve internal control. Furthermore, it aims to examine the calibre of Pospay services provided by PT Pos Indonesia KCU Jember and evaluate the internal control mechanisms implemented for funds produced from Pospay counter services. This study utilises descriptive qualitative research approaches. Data or information collection procedures are executed by the process of observation, interviews, and documentation to authenticate the obtained information or data.